Aspects of Indigenous Law as the Spearhead of Law Implementation in the Environmental Field - Maria Francisca M (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Local wisdom is a content of customary law and a valuable and ingrained heritage in every society, by continuing to preserve customary norms, and cultural values, which are passed down in the form of environmental management activities. Communities that still uphold local wisdom gain balance and live alongside nature. By upholding customary law, nature is given benefits by providing comfort in obtaining life materials from the environment because in that society they maintain the environment and prevent environmental damage. The advancement of technology has caused the loss of local wisdom resulting in barren forests and automatically killing springs, in addition to the river environment which has become dirty and unmaintained. This research is descriptive analytical and exploratory, to obtain an overview of customary law in local wisdom that can protect water sources and the river environment. As normative research, data is obtained through tracing legal documents. Return elements of customary law in community life to develop local wisdom. The principle of local wisdom is to synergize with nature so that the use of water resources is used sufficiently, not excessively, and provides prohibitions that aim to maintain the sustainability of water sources. By using sufficient water, the use of natural resources will also be used sufficiently by paying attention to prohibitions that aim to preserve the environment, in this case not clearing forests for plantations or settlements will automatically create sustainable forests and water sources will be maintained.Keywords: Environmental Sustainability, Indigenous Law.